Blocking of α1β1 and α2β1 adhesion molecules inhibits eosinophil migration through human lung microvascular endothelial cell monolayer - Stanisława Bazan-Socha (Postępy Higieny i Medycyny Doświadczalnej, 2014)
In cell trafficking to the airways in asthma, among integrins the most important are those containing α4 and β2 subunits. We have previously shown that also blocking of collagen receptors, α1β1 and α2β1 integrins, inhibits transmigration of eosinophils of asthmatic subjects through a monolayer of skin microvascular endothelial cells seeded on collagen IV coated inserts. However, it was not clear whether this observation was limited to asthma or depended on the type of microvascular cell and collagen IV used as a base. In the current study we performed a transmigration assay using human lung microvascular endothelial cells seeded directly on a plastic surface as a base and blood cells isolated from 12 representatives of each of two groups, asthmatics and healthy donors, by gradient centrifugation, followed by immunomagnetic negative separation of eosinophils. Isolated eosinophils and peripheral blood mononuclear cells (PBMC) were inhibited by snake venom-derived integrin antagonists including viperistatin and VP12, as inhibitors of α1β1 and α2β1 integrin, respectively, and VLO5 and VLO4, as inhibitors of α4β1 and α5β1 integrin, respectively. All snake venom-derived anti-adhesive proteins were effective in inhibiting eosinophil transmigration, whilst only VLO5 and VLO4 reduced PBMC mobility in this assay. This observation was similar in both groups of subjects studied. α1β1 and α2β1 integrins could be involved in transmigration of eosinophil to the inflammatory site. Migratory inhibition was observed in asthma subjects as well as in healthy donors, and did not depend on origin of endothelial cells or the extracellular matrix component used as a base.